Carrier heating and its effects on the current-voltage relations of conventional and hot-carrier solar cells: A physical model incorporating energy transfer between carriers, photons, and phonons. (August 2019) - Tsai, Chin-Yi
Highlights: Carrier intraband energy relaxation is incorporated into the Shockley-Queisser model for conventional solar cells and the Ross-Nozik model for hot-carrier solar cells. The effects of carrier heating on the current-voltage characteristics are investigated for GaAs, InP, GaSb, and InAs optical absorbers. Carriers in hot-carrier solar cells should be extracted with selective-contact energy larger than their quasi-Fermi-level separation in order to make devices work with extraction cooling, rather than recombination heating. Abstract: Theoretical models and frameworks are developed to investigate the effects of carrier heating on conventional and hot-carrier solar cells. They incorporate intraband carrier energy relaxation into the Shockley-Queisser model for conventional solar cells and the Ross-Nozik model for hot-carrier solar cells. Explicit formulas are presented to calculate intraband carrier energy relaxation rates via the interactions of polar longitudinal optical phonons and deformation-potential longitudinal and transverse optical phonons. These formulas incorporate the decay processes and phonon bath sharing of optical phonons. The effects of carrier heating on the current-voltage characteristics of conventional and hot-carrier solar cells are investigated and discussed for GaAs, InP, GaSb, and InAs materials. This paper will particularly discuss the differences between extraction cooling in hot-carrier solar cells and recombination heating from stimulated photon emissions in semiconductor lasers. It will prove that carriers in hot-carrier solar cells need to be extracted with a selective-contact energy larger than their quasi-Fermi-level separation in order to make devices work with extraction cooling, rather than recombination heating.